The influence of digital technologies on the formation of the image of the library - Yanchukov Oleksandr (Наукові праці Національної бібліотеки України імені В.І. Вернадського)

(untitled)
The purpose of the article is to consider the impact of digital technologies on the formation of the image of Ukrainian public libraries in the context of modern challenges using the example of the Alexandria City Centralized Library System. Methodological basis. The principle of unity of interconnection with modern conditions, sociocommunicative and structural-functional approaches and methods of analysis and synthesis, generalization and descriptive are applied. Scientific novelty. For the first time, the influence of digital technologies on the effectiveness of the positive image of Ukrainian public libraries in the face of modern challenges is highlighted using the example of the Alexandria City Centralized Library System. Conclusions. Today, the active introduction of digital technologies into the practice of Ukrainian public libraries in general and the Alexandria City Centralized Library System in particular, on the one hand, has a positive impact on the formation of the image of libraries in the face of modern challenges, and on the other, significantly increases the number of readers (including temporarily displaced persons with children) and users who, in particular, live far outside Ukraine, but are interested in the history of the Kirovohrad region. All library activities of the Alexandria City Centralized Library System, as well as all Ukrainian public libraries, are aimed at the assimilation of the achievements of universal culture, are client-oriented, diverse in topics and free of charge. The Central City Library of the Alexandria City Centralized Library System plays an important sociocultural role in the life of the community. The Central City Library of the Alexandria City Centralized Library System is a hub of digital education, a modern information and cultural center of the city, which is optimally oriented to the requirements of the time and the information needs of users. The image of the libraries of the Alexandria City Centralized Library System as library institutions - reliable partners of local residents - is effectively influenced by their presence in the media space through their own YouTube channel, Facebook, Telegram, and Instagram pages.